Effect of Supplementation of Rumen-Protected Methionineand Lysine on Digestibility and Rumen Fermentation inFemale Calves - Metiya, Ashish K; Vahora, Safi G; Lunagariya, Pravin M; Shekh, Makbul A; Chauhan, Ujjaval K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was performed on crossbred (Kankrej×HF) female calves to evaluate the supplementation effect of rumen-protected methionine (RPM) and lysine (RPL) on digestibility of nutrients and rumen fermentation. For this study, twelve crossbred female calves were randomly allotted to two groups T1 and T2 on their body weight for a period of 98 days. Calves in the T1 group were fed basal TMR to meet the nutrient requirement as per ICAR (2013) standard and those in T2 were fed basal TMR same as T1 + 2 g/kg DM RPMand 6 g/kg DM RPL. The digestion trial was conducted on all the experimental calves during the 11th week of experimental period. The collection period was of 7 days during which the representative samples of daily TMR fed, leftover and output of faeces were collected and analyzed. The rumen studies were carried out during last month of experiment. The rumen liquor samples were collected from experimental animals at 0, 2, 4 and 6 h post-feeding through a stomach tube against negative pressure created by a suction pump. There was no effect on digestibility coefficients of nutrients between the treatment groups. However, the percent fecal nitrogen excretion as nitrogen intake (N efficiency) was significantly (p<0.05) lower in T2 as compared to T1. Thus supplementation of RPM and RPL prevent the detrimental effect of ammonia and GHG on environment by improving nitrogen efficiency. The crossbred female calves fed basal TMR supplemented with rumen protected methionine and rumen protected lysine improved soluble nitrogen and total nitrogen of strained rumen liquor. However, ruminal pH, total volatile fatty acids, ammonia nitrogen, and non-protein nitrogen did not show any significant difference among treatment groups.